Giant omental lipoblastoma and CD56 expression - Go Miyano; Takuo Hayashi; Atsushi Arakawa; Shumpei Goto; Geoffrey J Lane; Tadaharu Okazaki; Atsuyuki Yamataka (Wolters Kluwer Medknow Publications, 2013)
We report a case of giant omental lipoblastoma in a 13-month-old boy, which was treated successfully by total excision. Tumor cells were positive for S100, CD34 and CD56. This is the first report of lipoblastoma expressing CD56, a fact that could be used to differentiate lipoblastoma from liposarcoma.